PENGEMBANGAN INFRASTRUKTUR PROGRAM PENDIDIKAN VOKASI UNTUK MEMENUHI TUNTUTAN DUNIA KERJA - Eva Devi Sofyawati; Mohammad Fakry Gaffar; Aan Komariah; Abdul Azis Wahab (Universitas Pendidikan Indonesia, 2023)
This research aimed to examine the infrastructure development of vocational education programs and the role of leadership and management in accordance with the demands of the workforce. The research applied qualitative method and was conducted at a state Polytechnic in Bandung with participants from the leadership, Study Programs, lecturers and instructors. The results of the study indicated that infrastructure development and the role of leadership and management had been carried out well to meet the needs of the workforce. However, management in the program of recruiting educators from industries and cooperation with other parties in the development of facilities needed an improvement.